Development of an IgG4-RD Responder Index - Carruthers, Mollie N. (Hindawi Publishing Corporation, 2012)
IgG4-related disease (IgG4-RD) is a multiorgan inflammatory disease in which diverse organ manifestations are linked by common histopathological and immunohistochemical features. Prospective studies of IgG4-RD patients are required to clarify the natural history, long-term prognosis, and treatment approaches in this recently recognized condition. Patients with IgG4-RD have different organ manifestations and are followed by multiple specialties. Divergent approaches to the assessment of patients can complicate the interpretation of studies, emphasizing the critical need for validated outcome measures, particularly assessments of disease activity and response to treatment. We developed a prototype IgG4-RD Responder Index (IgG4-RD RI) based on the approach used in the development of the Birmingham Vasculitis Activity Score for Wegener's granulomatosis (BVAS/WG). The IgG4-RD RI was refined by members of the International IgG4-RD Symposium Organizing Committee in a paper case exercise. The revised instrument was applied retrospectively to fifteen IgG4-RD patients at our institution. Those scores were compared to physician's global assessment scale for the same visits. This paper describes the philosophy and goals of the IgG4-RD RI, the steps in the development of this instrument to date, and future plans for validation of this instrument as an outcome measure.